Maladaptive eating habits in judo athletes and psychological side effects: case studies - Zorzi, E.; Zandonai, T. (Emerging Trends in Drugs, Addictions, and Health, 2024)
Originating in 19th-century Japan, judo blends traditional martial arts with modern educational principles. As a martial art rooted in the Budo tradition, it embodies a philosophy focused on the harmony of mind and body. In the West, however, the discipline evolved with an emphasis on competition and athleticism, which has led to increased competitive pressures among athletes. We report here the case studies of two Italian judokas who retired due to the development of unhealthy eating habits, extreme exercise and other unwanted psychological distress. It will be argued that the prevalent practice of weight cutting in combat sports poses substantial physical and psychological risks, particularly for young athletes. Despite regulatory efforts to mitigate extreme weight loss methods, there remains a critical need for improved education on safe practices. It sheds light on the complex interplay between athletic success, physical and mental health, and cultural perceptions of Judo in contemporary society.